PETISI 50 DAN DAMPAKNYA PADA MASAORDE BARU TAHUN 1980-1985 - Aprilinata, Andriko; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:The Indonesian nation in its history has experienced several government regimes with their respective advantages and disadvantages. The New Order began when there was a transfer of power from President Soeharto to General Suharto. The transfer of power was written in a March Order (Supersemar) in 1966, made by President Soekarno. The New Order was confirmed in MPRS Decree No. IX / MPRS / 1996 General Suharto to carry out the power of government. During the New Order Government, the Indonesian people naturally experienced various political problems, namely the existence and development of the 50th Petition during the New Order era. The purpose of this paper is as follows: (1) To find out the background of the formation of Petition 50 during the New Order, (2) To find out the process of preparing Petition 50 during the New Order, (3) To find out the government's response to Petition 50 during the Order New In 1980-1985, (4) To find out the impact of the Petition 50 during the New Order in 1980-1985. In this study the authors used the historical method. What is meant by the historical method is a research method used to make a systematic and objective reconstruction of the past by collecting data, evaluating in detail the evidence in detail to explain the facts and obtain strong conclusions. The 50th petition began when President Soeharto's speech in Pekanbaru in 1980 and the second speech in Cijantung on 16 April 1980 used Pancasila to bring down political opponents. This 50 petition had an impact on the figures involved because it was considered against PresidentSoeharto.KeyWords: New Order, Petition 50, Impact of Petition 50